Divergent habitat use of two urban lizard species. Issue 1 (23rd November 2017) - Winchell, Kristin M.; Carlen, Elizabeth J.; Puente‐Rolón, Alberto R.; Revell, Liam J.
Abstract: Faunal responses to anthropogenic habitat modification represent an important aspect of global change. In Puerto Rico, two species of arboreal lizard, Anolis cristatellus and A. stratulus, are commonly encountered in urban areas, yet seem to use the urban habitat in different ways. In this study, we quantified differences in habitat use between these two species in an urban setting. For each species, we measured habitat use and preference, and the niche space of each taxon, with respect to manmade features of the urban environment. To measure niche space of these species in an urban environment, we collected data from a total of six urban sites across four different municipalities on the island of Puerto Rico. We quantified relative abundance of both species, their habitat use, and the available habitat in the environment to measure both microhabitat preference in an urban setting, as well as niche partitioning between the two different lizards. Overall, we found that the two species utilize different portions of the urban habitat. Anolis stratulus tends to use more "natural" portions of the urban environment (i.e., trees and other cultivated vegetation), whereas A. cristatellus more frequently uses anthropogenic structures. We also found that aspects of habitat discrimination in urban areas mirror a pattern measured in prior studies for forested sites in which A. stratulus was found to perch higher than A. cristatellus and preferred lower temperatures and greater canopy cover. In our study, we found that the multivariate niche space occupied by A. stratulus did not differ from the available niche space in natural portions of the urban environment and in turn represented a subset of the niche space occupied by A. cristatellus . The unique niche space occupied by A. cristatellus corresponds to manmade aspects of the urban environment generally not utilized by A. stratulus . Our results demonstrate that some species are merely tolerant of urbanization while others utilize urban habitats in novel ways. This finding has implications for long‐term persistence in urban habitats and suggests that loss of natural habitat elements may lead to nonrandom species extirpations as urbanization intensifies. Abstract : We quantified differences in habitat use and niche space between two species of arboreal lizards ( Anolis cristatellus and A. stratulus ) in an urban setting. Overall, we found that the two species utilize different portions of the urban habitat with one species using more "natural" portions of the habitat and the other exploiting manmade portions of the habitat. Our results demonstrate that some species are merely tolerant of urbanization while others use urban habitats in novel ways, which has implications for adaptation and long‐term persistence in urban habitats.